The causes effects and the mediation roles of major actors in the Russian-Ukraine conflict - Jackson Timiyan; F. A. Sanubi; E. V. Clark (Qualitative Research of Business and Social Sciences, 2024)
This paper examines the causes, effects, and mediating roles of major actors in the Russian-Ukrainian conflict. The causes are rooted in historical, political, and territorial disputes, with Russia’s opposition to Ukraine's Western alignment playing a central role. The conflict has led to devastating humanitarian, economic, and geopolitical consequences, affecting not only Ukraine and Russia but also global markets and international relations. The paper also examines the efforts of key actors, including the United Nations, the European Union, the United States, and other international actors, to mediate the conflict through diplomacy, sanctions, and humanitarian assistance. Through this analysis, the paper examined the complexity of the conflict and the challenges of achieving peace. This paper concluded that the ongoing conflict has had dire economic consequences not only in the conflict zone but also globally. Africa and Asia are most affected because both regions are net exporters of food, petroleum products, fertilizers, and Steel to many countries worldwide. The paper recommended, among others, that the unilateral sanctions on Russia by the United Nations and other international actors will further worsen the conflict and impede the resolution process, and that the United Nations should step down its sanctions and mediation roles and allow states with a relatively neutral posture to mediate between Russia and Ukraine with a view to achieving rapprochement.